CASE REPORTSLymphangioleiomyomatosis as a rare cause of recurrent pneumothorax in women - Wojtyś, Małgorzata; Rogoziński, Paweł; Alchimowicz, Jacek; Wandzel, Piotr; Bubel, Adam; Grodzki, Tomasz; Bruliński, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
This paper presents five cases of women, aged between 25 and 44, treated surgically for pneumothorax in the course of lymphangioleiomyomatosis (LAM). Initially, they were treated by means of suction drainage of the pleural cavity, which was then followed by surgical procedures (resection of lung tissue with emphysematous bullae, pleurectomy, chemical pleurodesis with talc or doxycycline). All the operations were performed as minimally invasive procedures (VATS). In three women bilateral pneumothorax was observed, in one right-sided recurrent pneumothorax, and in one right-sided recurrent pneumothorax and left-sided pneumothorax were revealed. Tests revealed the presence of renal angiomyolipoma in two women and suspicion of renal angiomyolipoma in one patient. One of the patients was operated on due to uterine fibroids at the age of 36, and was treated for chylothorax. The surgical procedures applied were symptomatic. At present, lung transplantation is an essential method of therapy in the final period of LAM.